Effects of Halal Awareness, Service Quality and Promotion on Visitor Decisions Through Destination Imagery as a Mediator - Sunarmo, Sunarmo; Thurisaina, Mihda; Amri, Andi; Sagita, Ardio (UIN Sunan Gunung Djati Bandung, 2024)
Indonesia has a diversity of destinations and natural and cultural wealth; major assets that other countries might not have. Tourists' desire to travel is undoubtedly diverse. Hence, the Ministry of Tourism and Creative Economy of the Republic of Indonesia carried out promotions to increase the number of tourist visits by providing halal tourism locations that promoted the Muslim-friendly concept. This study determines the impact of halal awareness, service quality, and promotion on visitor decisions through destination imagery. The research method was descriptive quantitative, incorporating a purposive sampling technique to select participants who are visitors or people who have visited Kota Tua. The present study data were obtained by distributing questionnaires to 150 respondents who had visited Kota Tua tourist attractions in the past six months. The data analysis technique used was path analysis using SPSS software. The Cronbach's Alpha value for every variable was greater than 0.60, which implies the questions were trustworthy and it was possible to use each one. Based on the path analysis, halal awareness, service quality, and promotion impact on destination imagery has an R Square (R2) of 0.364 or 36.4%. The impact of halal awareness, service quality, and promotion on visitor decisions has an R2 of 0.548 or 54.8%. The findings indicated that halal awareness has a significant impact on destination imagery. Service quality promotion did not have a significant impact on destination imagery. Halal awareness and service quality did not significantly impact visitor decisions. Promotion and destination imagery had a significant impact on visitor decisions.